Effect of neuromuscular electrical stimulation on lip strength and closure function in patients with dysphagia after stroke - Kim, Won-Jin; Park, Ji-Su; Oh, Dong-Hwan (Journal of Physical Therapy Science, 2017)
[Purpose] This study aimed to investigate the effect of neuromuscular electrical stimulation (NMES) on lip strength and closure function of patients with dysphagia after stroke. [Subjects and Methods] Eight patients with dysphagia were recruited. NMES was applied to the orbicularis oris muscle. All the participants received NMES for 30 min/d, 5 d/wk, for 4 weeks. Lip strength was measured using the Iowa Oral Performance Instrument. To assess lip closure, the lip closure subitem of the videofluoroscopic dysphagia scale was used. [Results] Lip strength showed significant improvement and lip closure function showed a significant decrease. [Conclusion] This study demonstrates that NMES is useful for improving lip strength and closure function.